PENGARUH KERAPATAN VEGETASI TERHADAP FENOMENA URBAN HEAT ISLAND DI KOTA SURABAYA - Yovita Inggar Mawardi; Hidayati, Isti (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2025)
Since 2010, the Surabaya City Government has initiated efforts to increase and improve the amount of Green Open Space (GOS). However, the temperature in Surabaya City continues to rise each year, indicating the presence of the Urban Heat Island (UHI) phenomenon. This condition presents an interesting case to study, particularly regarding the role of green open spaces in mitigating UHI. Using a quantitative deductive approach through land surface temperature (LST) calculations, Moran’s I analysis, and spatial correlation, this study aims to examine the relationship between vegetation density (as a representation of green open space) and the UHI phenomenon in Surabaya City. The LST analysis results show a significant increase in UHI from 2013 to 2023 with a random spatial pattern. Furthermore, the Moran’s I and spatial correlation analyses reveal a negative but very weak correlation between UHI and vegetation density. This finding explains why the expansion of green open spaces has not yet been effective in reducing UHI in Surabaya City.